Three debts paid - Perry, Anne (A Daniel Pitt novel, 2022)
"A serial killer is on the loose, and may have a hidden connection to young barrister Daniel Pitt's university days, in this intricately woven mystery from New York Times bestselling author Anne Perry. A serial killer is roaming the streets of London, and Daniel Pitt's university chum Ian, now a member of the police, is leading the search. The murders are keeping his mind occupied, but when Ian learns that their old professor, Nicholas Wolford, has been charged with plagiarism, he takes the time to personally ask Daniel to defend their beloved teacher. For help catching who Londoners are now calling the "Rainy Day Slasher," Ian also enlists Daniel's good friend Miriam fford Croft, now back from school and a fully qualified pathologist. As the murders continue, Miriam can't help but notice inexplicable links that have been overlooked by Daniel and Ian. In their concern to defend their former professor, are the two university friends blind to a far worse crime that has been committed?"--